UTILIZING RASCH MODEL AS NOVEL ANALYSIS OF STUDENTS’ CRITICAL THINKING IN PHYSICS - Qudratuddarsi, Hilman; Jumriani, Jumriani; Yanti, Meili; Ramadhana, Nurhikma; Dewi, Hefi Rusnita (Jurnal Pembelajaran Sains, 2025)
There are numerous reported studies to find the best way of teaching physics, but their quantitative analysis merely depends on some inferential statistics comprising ANCOVA, t-test etc. Those analysis do not generate detailed information of student’s abilities, therefore this study analyze the effects of double-loop problem solving teaching methods towards student’s critical thinking using Rasch analysis. In this study, the samples were divided into experimental group and control group with 28 students and 25 students respectively. After the intervention, their critical thinking was measured using instrument that has been validated and pilot tested using Rasch analysis by considering their reliability, item fit statistics, and unidimensionality. After data analysis, based on person measure, it was found that there is statistically significant post-test logit score between experiment and control class with pre-test as covariate, p value